-6b=0

Simple and best practice solution for -6b=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6b=0 equation:


b in (-oo:+oo)

-6*b = 0

-6*b = 0 // : -6

b = 0

b = 0

See similar equations:

| -2+m=-1 | | m+7=11 | | 2x-9=4x | | 16+n=36 | | d+4=-4 | | t-5=6 | | 8=t+2 | | 3w=21 | | 3=n-7 | | 7x^2-24x+9=0 | | (x^3+2x+2)(x^2-x-1)=0 | | 19=k+10 | | 7x^2-24x+0=0 | | 3=m+5 | | 19v=152 | | (x^2+2x+6)(5x^2+2)=0 | | m/-7=4 | | k+6=-6 | | w+8=-2 | | -3+m=-6 | | m-2=-1 | | d+1=-7 | | -6a=-36 | | (7x^2+5x-1)(x^2-6x+9)=0 | | 3+n=11 | | 9+d=10 | | w/2=-7 | | (18+3x)/4=19.88 | | d/3=-4 | | (18+3x)/3=19.88 | | 3n=33 | | -8=a-9 |

Equations solver categories